Supernatural Snag Mortuary - Adelaide de Menil (1968)
On the post was a supernatural snag in human form at the top and a killer whale at the base, both of which have been broken apart by plant growth. Originally the pole featured a front plaque that was plain, with the high dorsal fin of the killer whale projecting above the plaque.